Money Market Reform in Korea and Its Effects on the Overnight Call–Repurchase Agreement Rate. Issue 9 (1st September 2016) - Suh, Hyunduk
ABSTRACT: The Korean government implemented money market reform after the global financial crisis, aiming to develop the repurchase agreement (RP, repo) market. In this article, I analyze the reform and its effects on money markets. Results show that the reform strengthened the functionality of the RP market and the monetary policy transmission channel to it. The error correction model indicates that although the adjustments to the equilibrium occurred through the call rate during the global financial crisis, they were processed through the RP rate in later periods. The ability of the RP rate to inform market liquidity conditions has improved.